Strategi Marketing Public Relations Persib Bandung Melalui Program Sponsorship - Fauzi, Achmad; Muchtar, Khoiruddin; Fuad, Ahmad (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
The world has entered an era where all information is easily obtained via the internet. Every person or business actor is required to be able to have a strong character and characteristic so that it is easier to recognize and remember amid the many innovations that are present in the current era. This study aims to find out how the tactics of the Persib Bandung Marketing Public Relations team use the Three Ways Strategy concept developed by Philip Kotler. This research was conducted using a qualitative approach. The method used is descriptive analysis in the presence of primary and secondary data through data collection techniques, namely in-depth interviews, observation, and documentation. The results of this study can be concluded that the strategy of the Persib Bandung Marketing Public Relations team uses the concept of Three Ways Strategy through the Sponsorship program as follows: 1) The Pull strategy in attracting public attention is carried out by carrying out massive publications and involving Bobotoh in various activities held by Persib Bandung; 2) The Push (pull) strategy in encouraging marketing success is carried out by making Persib Bandung players as Brand Ambassadors, as well as expanding marketing evenly; 3) Pass strategy (creating opinions) in creating favorable opinions is carried out by organizing events, as well as forming an image by selecting sponsors.